MODEL KEMITRAAN DALAM PENGELOLAAN TAMAN NASIONAL KUTAI PROPINSI KALIMANTAN TIMUR - , SUMIDI, Prof. Dr. M. Baiquni, MA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kutai National Park is a conservation area which has a complex problem. Kutai National Park is located between developed cities (Bontang and Sangata) and surrounded by corporate exploitation of natural resources (oil, gas, forest industry, and coal). These conditions put the Kutai National Park as an 'island preservation' is susceptible to damage. One effort was developed in the management is partnership with of companies around that are members of the Friends of Kutai National Park. This study aims to assess: (1) background formation of partnerships in the management of Kutai National Park